Fixed-time attitude tracking control for rigid spacecraft. (March 2020) - Zou, An-Min; Kumar, Krishna Dev; de Ruiter, Anton H.J.
Abstract: The problem of fixed-time attitude tracking control for rigid spacecraft is addressed in this paper. Based on the backstepping technique and the idea of "adding a power integrator", a novel fixed-time attitude control law is proposed. The control scheme derived here is continuous and nonsingular, and can guarantee the attitude tracking errors converging to the origin within fixed time if there are no uncertainties and measurement noises and to a small bounded region around zero if there are uncertainties and measurement noises. Finally, numerical simulations are presented to demonstrate the effectiveness of the proposed scheme.